Час потехи: стихи / Б. В. Заходер - Заходер Борис Владимирович (Для самых маленьких, 2003)
Экземпляры: (20200716) / Инвентарный номер: 30407 / Цена: 20.20 / Сис.шифр: Р2 / Авт.знак: З-38 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6